2017
DOI: 10.1021/acs.jpcc.6b11047
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Surface Plasmon Resonance in Sub-Stoichiometry Molybdenum Oxide Nanodots through Charge Carrier Control Technique

Abstract: Semiconductor nanocrystals are intriguing because they show surface plasmon absorption features like noble metallic nanoparticles. In contrast with metal, manipulation of their unique plasmonic resonance could be easily realized by the free-carrier concentration. Here, it is demonstrated that MoO3–x nanodots can exhibit striking surface plasmon resonance located at near-infrared region under treatment of two different reducing agents. Furthermore, the tunable resonance mode has been achieved through appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…2.25). The abovementioned results present the cysteine could reduce the MoO 3 step by step and produce NPs with different valences, which is similar to the NaBH 4 reduction effect …”
Section: Figuresupporting
confidence: 56%
“…2.25). The abovementioned results present the cysteine could reduce the MoO 3 step by step and produce NPs with different valences, which is similar to the NaBH 4 reduction effect …”
Section: Figuresupporting
confidence: 56%
“…29 nm;F igure 1d). [10] TheU V/Vis and CD spectra were then utilized to investigate the chiroptical activity of l-a nd d-Cys capped MoO 3Àx and MoO 2 .The absorption spectra clearly reveal that the surface plasmonic peak and MLCT peak could be tuned via the adjustment of capping ligand concentration (Figure 3b). TheX -ray surface photoelectron spectrum (XPS) results indicate that the molybdenum element valence could decrease from Mo VI to Mo IV during reduction reaction progressively (Figure 2).…”
Section: Chiralinorganicnanocrystals(ncs)asanemergingareahasmentioning
confidence: 99%
“…Theabovementioned results present the cysteine could reduce the MoO 3 step by step and produce NPs with different valences,w hich is similar to the NaBH 4 reduction effect. [10] TheU V/Vis and CD spectra were then utilized to investigate the chiroptical activity of l-a nd d-Cys capped MoO 3Àx and MoO 2 .The absorption spectra clearly reveal that the surface plasmonic peak and MLCT peak could be tuned via the adjustment of capping ligand concentration (Figure 3b). With the addition of small amount of l-ord-Cys,the MoO 3Àx NPs exhibit only strong NIR absorption band at around 823 nm.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Therefore it can be concluded that the LSPR is easily influenced by the effective local medium index. In these cases, the obtained MoO 3− x nanodots dispersed in different solvent can be viewed as a molecule sensing system, and the LSPR properties can be effected by the affinity between MoO 3− x nanodots and solvent molecules, not only the refractive index as reported in the literature …”
Section: Figurementioning
confidence: 99%